2018
DOI: 10.3390/nu10080988
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Gut Commensals in Reinforcing Intestinal Barrier Function and Alleviating Inflammation

Abstract: The intestinal microbiota, composed of pro- and anti-inflammatory microbes, has an essential role in maintaining gut homeostasis and functionality. An overly hygienic lifestyle, consumption of processed and fiber-poor foods, or antibiotics are major factors modulating the microbiota and possibly leading to longstanding dysbiosis. Dysbiotic microbiota is characterized to have altered composition, reduced diversity and stability, as well as increased levels of lipopolysaccharide-containing, proinflammatory bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
340
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(383 citation statements)
references
References 169 publications
(217 reference statements)
5
340
0
5
Order By: Relevance
“…Additionally, Alistipes has been identified as one of the top ten most abundant genera associated with human colorectal carcinoma, and it has been demonstrated to potently induce inflammation and tumorigenesis . Previous studies have shown that the Lachnoclostridium , Blautia, and Eubacterium hallii genera can produce short‐chain fatty acids (SCFAs) through the fermentation of soluble fiber . SCFAs have been shown to play a protective role in chronic diseases that involve the regulation of intestinal immune function, as well as in the maintenance of gut barrier .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Alistipes has been identified as one of the top ten most abundant genera associated with human colorectal carcinoma, and it has been demonstrated to potently induce inflammation and tumorigenesis . Previous studies have shown that the Lachnoclostridium , Blautia, and Eubacterium hallii genera can produce short‐chain fatty acids (SCFAs) through the fermentation of soluble fiber . SCFAs have been shown to play a protective role in chronic diseases that involve the regulation of intestinal immune function, as well as in the maintenance of gut barrier .…”
Section: Discussionmentioning
confidence: 99%
“…35 Previous studies have shown that the Lachnoclostridium, Blautia, and Eubacterium hallii genera can produce short-chain fatty acids (SCFAs) through the fermentation of soluble fiber. 36,37 SCFAs have been shown to play a protective role in chronic diseases that involve the regulation of intestinal immune function, as well as in the maintenance of gut barrier. 38 The effect of antibiotics on gut microbiota has long been a concern in the implementation of H pylori eradication.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs via microbiota effects on both innate and adaptive immunity (Table 1; Fig. 1) [212, 1529]. The microbiota differs depending on the region of the GIT (oesophagus, stomach, upper and lower intestine, colon), but this review will focus on the colonic microbiota where an estimated 70% of the GIT microbiota reside [4].…”
Section: The Healthy Microbiota and Its Role In Immune Homeostasismentioning
confidence: 99%
“…There is also hope that probiotics or commensal organisms improve intestinal barrier function66; however, the evidence to date is sparse, often based on animal models rather than human studies, the beneficial effect may be through the effects of butyrate and the documented effects have been reported for the organism Akkermansia municiphila 67. There is a microintegral membrane protein (MIMP) that is the smallest domain of surface layer protein from Lactobacillus plantarum .…”
Section: Introductionmentioning
confidence: 99%